Circulating inhibitor of gonadotropin releasing hormone secretion by hypothalamic neurons in uremia - Daschner, Markus; Philippin, Bärbel; Nguyen, Trang; Wiesner, Rudolf J.; Walz, Claudia; Oh, Jun; Sandow, Jürgen; Mehls, Otto; Schaefer, Franz (Kidney international, 2002)
Circulating inhibitor of gonadotropin releasing hormone secretion by hypothalamic neurons in uremia. - Background - Previous studies have suggested a neuroendocrine defect underlying uremic hypogonadism, characterized by a reduced secretion of gonadotropin-releasing hormone (GnRH) and luteinizing hormone (LH).